(untitled) (ECO revista académica, 2024)
A measurement of the size of informal economy in Guatemala from 1960 to 2017 is proposed in this work throughout a monetary method. Thus, the variations of the monetary aggregates and the main variables that determine the movements of cash in the country are examined. It is estimated that the shadow economy in Guatemala has been on average 47 % over time from 1960 to 2017 with a standard deviation of 6 percentage points, without major structural changes. After the statistical analysis it is concluded that the Shadow Economy in Guatemala shows mean reversion and transitory shocks.